2022
DOI: 10.1002/jbt.23243
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and methylmercury differentially modulate hepatic cytochrome P450 1A1 and 1A2 in vivo and in vitro

Abstract: The cytochrome P450 1 A (CYP1A) subfamily enzymes are involved in the metabolic activation of several xenobiotics to toxic metabolites and reactive intermediates, resulting ultimately in carcinogenesis. Mercury and halogenated aromatic hydrocarbons (HAHs), typified by 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD), are persistent environmental pollutants involved in the modulation of aryl hydrocarbon receptor (AHR) gene battery, including cytochrome P450 (CYP) genes. We previously investigated the effect of coexpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This suggests that MeHg enhances the de novo synthesis of Nqo1 RNA, similar to the effect observed with TCDD, which induces this gene transcriptionally through XRE-ARE pathway. Third, MeHg was capable of increasing basal and inducible ARE-luciferase activity, however, we previously reported that MeHg did not alter XRE-luciferase activity using same cell line ( Alqahtani et al, 2023 ). Therefore, these findings imply that ARE (or NRF2) pathway, but not that of XRE (or AHR), may be solely involved in the NQO1 transcriptional regulation upon MeHg exposure.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This suggests that MeHg enhances the de novo synthesis of Nqo1 RNA, similar to the effect observed with TCDD, which induces this gene transcriptionally through XRE-ARE pathway. Third, MeHg was capable of increasing basal and inducible ARE-luciferase activity, however, we previously reported that MeHg did not alter XRE-luciferase activity using same cell line ( Alqahtani et al, 2023 ). Therefore, these findings imply that ARE (or NRF2) pathway, but not that of XRE (or AHR), may be solely involved in the NQO1 transcriptional regulation upon MeHg exposure.…”
Section: Discussionmentioning
confidence: 81%
“…All remaining materials are from Fisher Scientific (Waltham, MA, USA). Further details about the used materials not mentioned above can be found in our previously published paper ( Alqahtani et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations